Numerical study of the circular opening effect on mechanical behaviour of rock under confinement - Gui, Yi Lin (2020)
Opening holes in rock including their size and distribution can affect the performance of rock-related structures. A good understanding on this will contribute to, for example, rock cavern design, and construction, tunnelling, and mining engineering. To improve the understanding, a comprehensive investigation of the opening hole effect on the rock mechanical behaviour under biaxial loading condition is carried out by virtue of a hybrid continuum-discrete element method. Laboratory specimens with both single hole and multi-hole of various radii are investigated and compared with the cases subjected to uniaxial compression. It is demonstrated that the confining pressure can increase both the stiffness and strength due to delaying the crack initiation and propagation. The increase due to the confining pressure is more evident for the compressive strength. For single hole specimens with 0.75 mm radius hole, the increase ratio of the compressive strength is a linear increasing function with width and the increase ratio ranges from 2.15 for the specimen with 3.5 mm width to 2.45 for 10 mm width. For the single hole specimen with 10 mm width, the increase ratio starts at 2.13 for the specimen with 0.75 mm radius hole, ascending to the peak of 2.37 for the specimen with 1 mm radius hole, followed by a decline to 2.2 for the specimen with 1.25 mm radius hole. However, for the multi-hole specimens, the increase ratio varies from 1.66 to 3.13. In addition, to verify the influence of confining pressure magnitude on the performance of the rock specimens, totalling 10 confining pressure levels are applied and modelled. The simulation results show that even though there are opening holes in the specimens, the simulated compressive strength generally follows the generalised Hoek-Brown model.